NOVEL SIRKUS POHON KARYA ANDREA HIRATA: KAJIAN STILISTIKA - Ayu Kristiana; Heru S.P. Saputra; Sri Mariati (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2019)
The goal of this study is revealing the stylistic elements found in the novel entitled Sirkus Pohon by Andrea Hirata, preceding by describing the relationship between structural elements. The research method is a qualitative method with descriptive analysis based on structural theoretical concepts and stylistics. The results of the study shows that the structural elements in the novel Sirkus Pohon have a relationship between one to other element namely title, theme, character, conflict, and setting. All these five elements form the wholeness of the story. In the field of stylistics, the aesthetics of the story can be obtained from the language potentiality namely diction, sentence style and figurative language. The figurative language created by the writer are metaphor, sentence style, and personification. The potential language used by Andrea Hirata cannot be separated from the sociocultural context and also the sleight of the writer. The writer presents an intellectual figure, whereas the contextual society is a traditional and poor. It twitters people of Malay in the inland Belitung who still innocence but full of intrigue. In this novel, the appearance of pomegranates is related to the problems of love, traditional beliefs, the revival of the traveling circus, and political issues. The author expresses the traditional beliefs contradicting to the author's logic or intellect.